Allometric Growth of Testes in Relation to Age, Body Weight and Selected Blood Parameters in Male Japanese Quail (Coturnix japonica) - Vatsalya, Vatsalya; Arora , Kashmiri L. (International Journal of Poultry Science, 2012)
The Japanese quail is very a valuable animal model for research in a variety of biological disciplines. The purpose of this study was to characterize and interrelate age-dependent testicular parameters with various blood constituents: blood glucose, plasma proteins and packed cell volume that are developing concurrently in the growing bird. Another objective of the study was to identify selective physio-anatomical markers for predicting the testicular growth and the onset of sexual maturity. Male Japanese quail hatchlings were raised in temperature controlled brooders for up to 3 weeks of age under a constant light and then shifted to hanging cages in an air conditioned room set at ~73° F under a 14L: 10D lighting system and ad libitum access to feed and water. Starting d8, a group of 8-10 birds of uniform size and weight were selected randomly at 4-day intervals up to d52 of age for the project. The birds were weighed and blood sampled using the brachial vein and Blood Glucose (BGL), Total Plasma Proteins (PP) and Packed Cell Volume (PCV) levels were measured prior to euthanization. The testes were removed and measured for weight, length, width and Volume (VOL). All the testicular measurements were then correlated with age and body weight. The left testes were larger than the right testes and their differences were evident at d36 of age. Testicular measurements also reflected two distinct growth surges at d28, d32 and d36 of age. Combined Testes Weight (CTW) and Combined Testes Volume (CTV) revealed a strong positive correlation with PCV and PP and a negative correlation with Blood Glucose Level (BGL). Accordingly, these measurements could serve as reliable markers of growth rate and sexual maturation in male Japanese quail.